2022
DOI: 10.2460/ajvr.21.02.0027
|View full text |Cite
|
Sign up to set email alerts
|

The bacteriome of the oral cavity in healthy dogs and dogs with periodontal disease

Abstract: OBJECTIVE To compare the bacteriome of the oral cavity in healthy dogs and dogs with various stages of periodontal disease. ANIMALS Dogs without periodontal disease (n = 12) or with mild (10), moderate (19), or severe (10) periodontal disease. PROCEDURES The maxillary arcade of each dog was sampled with a sterile swab, and swabs were submitted for next-generation DNA sequencing targeting the V1–V3 region of the 16S rRNA gene. RESULTS 714 bacterial species from 177 families were identified. The 3 most fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 41 publications
2
29
0
3
Order By: Relevance
“…Ruparella et al and team reported that saliva exhibited the lowest bacterial diversity, the buccal and the tongue dorsum mucosa had the most similar bacteria [ 33 ]. Moreover, the teeth area and the dental plaque were the selected area for the periodontal disease [ 31 , 32 , 67 , 70 , 76 78 ]. So, the oral swab sample from the tongue's dorsum mucosa and the mucosa of the hard palate of each dog was taken to compare the microbes among the three groups of dogs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Ruparella et al and team reported that saliva exhibited the lowest bacterial diversity, the buccal and the tongue dorsum mucosa had the most similar bacteria [ 33 ]. Moreover, the teeth area and the dental plaque were the selected area for the periodontal disease [ 31 , 32 , 67 , 70 , 76 78 ]. So, the oral swab sample from the tongue's dorsum mucosa and the mucosa of the hard palate of each dog was taken to compare the microbes among the three groups of dogs in our study.…”
Section: Discussionmentioning
confidence: 99%
“…It is a Gram-negative anaerobic bacterium strongly linked to advanced periodontal lesions [33][34][35] . In canines, the Porphyromonas genus is also proposed to be a potential pathogen linked to PD 22,25,31,32 . We observed an increased presence of the Porphyromonas genus correlated with escalating PD severity.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we sampled dental plaque using a micro-applicator to examine subgingival plaque. Several studies have reported that PD microbiomes can be monitored without targeting focal plaque 22,40,41 . A negative correlation existed between the relative abundance of Porphyromonas and gingivitis score 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Canine oral microbiota present similar number (around 350 bacterial taxa from 148 genera) but significantly different populations compared to the human ones 98 and is mainly colonized by Proteobacteria (45%), Bacteroidetes (25%) and Firmicutes (19%). Most abundant species are Porphyromonas cangingivalis and Porphyromonas gulae 99 , 100 . Regarding the other digestive compartments, studies have been mostly performed on faeces to avoid invasive procedures.…”
Section: Impact Of Body Size On Microbial Parametersmentioning
confidence: 99%